Graça RIO-TORTO, Alexandra Soares RODRIGUES, Isabel PEREIRA, Rui PEREIRA, Sílvia RIBEIRO. Gramática Derivacional do Português, Coimbra, Imprensa da Universidade de Coimbra, 2013. 512 pp. ISBN 978-986-26-0640-8 - Brito, Ana Maria (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.